Ca2+i and the pancreatic α cell – intrinsic regulation and dysfunction in type 2 diabetes - Kellard, J (2019)
In type 2 diabetes (T2D), elevated plasma glucagon concentration (hyperglucagonaemia) exacerbates hyperglycaemia due to inappropriate insulin secretion. Despite this, very little is known about why glucagon secreting α cells become dysfunctional.